Application cases in MIS - Morgan, James N. (McGraw Hill/Irwin, 2005)
An introductory level MIS business casebook, which requires the use of spreadsheet and database software and the Internet to solve managerial problems. It may be used as a standalone casebook or packaged with any of our introductory Management Information Systems textbooks. The book was developed to give students additional projects or exercises to apply the concepts of what they have learned in their course.